Citizen sources in the news: Above and beyond the vox pop?. (April 2017) - Kleemans, Mariska; Schaap, Gabi; Hermans, Liesbeth
Both within journalism and academia it is argued that citizen voices should have a greater prominence in news to counterbalance the virtual monopoly of elite sources. This study extends previous studies – showing increased presence of citizens in news – by investigating relevant but unanswered questions, namely, (1) whether there has been a change in their prominence relative to elite and civil society sources and (2) in which capacity citizens have been present in the past two-and-a-half decades. Moreover, (3) citizens' contribution to different story topics is explored. In this study, 1425 television news stories broadcast between 1990 and 2014 ( N = 2413 sources) are analyzed. Results show that citizen sources became more prominent at the cost of elite sources. However, elite sources still remain the primary definers in news. Citizens do not get a more substantive, relevant voice as they are primarily used as vox pops, regardless of story topic.